Analisis Transaksi Akad Istishna’ dalam Praktek Jual Beli Online - Rani Maylinda; Wirman Wirman (Jurnal Ilmiah Wahana Pendidikan, 2023)
Along with the development of technology in making transactions that are increasingly developing, there are many conveniences for people to shop. such as selling bells online known as e-commerce. By concluding that buying and selling transactions on shopee, tokopedia, lazada, bibli, bukalapak e-commerce have been widely used by the public today. Online buying and selling is buying and selling with a purchase system by ordering and paying at the beginning, in the middle, or at the end with a predetermined grace period using technological sophistication. There are also contracts used such as istisna contracts in carrying out this transaction. The purpose of this study is to examine more deeply the istisna contract in online buying and selling transactions. This paper uses a qualitative method with a descriptive approach. The analysis used uses content analysis, with more depth to the information found. The results of this study found out buying and selling transactions in Islam with istisna contracts, the basis of Shari'a, istisna parallel, and how the transaction formed.